2020
DOI: 10.2478/agri-2020-0005
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Texturally Different Soils After Application of Biochar Substrates

Abstract: Scientific studies show that the efficiency of biochar can be improved by its combination with other fertilisers. For this reason, fertiliser manufacturers are working to create products that combine biochar with other soil fertility enhancers suitable for different soil-climatic conditions. In this study, two types of biochar substrates (1. biochar blended with farmyard manure, and 2. biochar blended with farmyard manure as well as with digestate) at rates of 10 and 20 t/ha were applied alone or in combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…It was also found that generally, SWC increased with the increasing application rates of biochar (including reapplied treatments) at both fertilization levels (N1 and N2). Our findings on SWC are in line with recent studies by Barrrow [75], Agegnehu et al [76], Leelamanie [77], Liyanage and Leelamanie [78], and Šrank and Šimanský [79]. The positive effect of added biochar can partially be because of biochar's high sorption capacity and swelling ability, which result in an increase in the total porosity of the soils.…”
Section: Physical Properties Of Soilsupporting
confidence: 91%
See 1 more Smart Citation
“…It was also found that generally, SWC increased with the increasing application rates of biochar (including reapplied treatments) at both fertilization levels (N1 and N2). Our findings on SWC are in line with recent studies by Barrrow [75], Agegnehu et al [76], Leelamanie [77], Liyanage and Leelamanie [78], and Šrank and Šimanský [79]. The positive effect of added biochar can partially be because of biochar's high sorption capacity and swelling ability, which result in an increase in the total porosity of the soils.…”
Section: Physical Properties Of Soilsupporting
confidence: 91%
“…Biochar, with its large surface area and a large number of micropores, alters the average surface area of the soil, pore size distribution, and, thus, the water retention capacity of the soil [82]. The incorporation of biochar may enhance the specific surface area up to 4.8 times compared to unamended soils [83] and may also increase the presence of capillary pores [79].…”
Section: Physical Properties Of Soilmentioning
confidence: 99%
“…Mineral nitrogen applied to the soil can act as an accelerator speeding up the mineralization of organic matter [62], which can result in an increase of BD values. However, application of biochar in combination with N fertilization has a positive effect on the incorporation of biochar-especially into larger aggregates [62]-which helps to improve the soil structure [65] and ultimately reduce the BD values as was also confirmed in the results obtained by Šrank and Šimanský [64]. In our case, a significant decrease in BD was observed for biochar application and re-application at the dose of 10 t ha −1 in combination with 108 kg N ha −1 (B10 + N1 and B10 reap + N1) and at the second fertilization level (162 kg N ha −1 ) for biochar application at a dose of 20 t ha −1 (B20 + N2) and re-application at both doses (B10 reap + N2 and B20 reap + N2) (Table 5).…”
Section: Discussionmentioning
confidence: 55%
“…Due to its inert nature, biochar is often combined with other organic and mineral fertilizers to improve its effect in the soil [63,64]. Fertilization-especially with nitrogen-is a significant factor influencing BD.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information on the experimental design can be found in the work of Šrank and Šimanský [23]. Briefly, the experiment in Dolná Streda was established using the long segment method in autumn 2017 on 10 plots (one treatment = 90 m 2 ).…”
Section: Experimental Sites and Research Designmentioning
confidence: 99%